Determinants of eco-socially conscious consumer behavior toward alternative fuel vehicles. Issue 2 (1st February 2021) - Saleem, Muhammad Abid; Eagle, Lynne; Low, David
Abstract : Purpose: Climate change and global warming are acknowledged to be growing issues caused by emissions of greenhouse gases. Fuel-efficient or green cars offer a technological solution to reduce CO2 emissions from car exhaust. This study aims to draw on value–belief–norm (VBN) theory to provide an explanation of eco-socially conscious consumer behavior (ESCCB) related to the choice and use of personal cars. Design/methodology/approach: The data was collected from 1, 372 customers of the automobile industry of Pakistan, randomly drawn from 8 metropolitan cities. Partial least squares structural equation modeling is used to verify the hypotheses of the study. Findings: By using variance-based structural equation modeling, this study showed that the VBN theory is fully supported in the cultural context of Pakistan and behavioral context of ESCCB. More specifically, personal introjected norms of the customers proved to be strong predictors of ESCCB while personal integrated norms predicted eco-social purchase intentions well. Originality/value: To the best of the authors' knowledge, this is the only study of its kind that examines the VBN model in the context of a developing country, Pakistan, and for a category of behaviors rarely tested before, i.e. ESCCBs related to purchase and use of personal cars.